Gender Stereotyping and Limitations in Elementary School Student Participation - Serrano Arenas, Denys (2021)
This objective of this article is to identify concepts and gender stereotypes that limit student participation among students at a Mexican elementary school. A quasi-ethnographic method was used to describe and interpret data collected from one-on-one interviews conducted among of sixth graders (25 girls and 22 boys). Based on the analyzed results, it was concluded that gender stereotyping limited the participation of girls at school by portraying them as frail and overexerted from academic endeavours, whereas boys were described as stronger, but with sparse academic commitment and physical strength. Thus, gender stereotyping curbs student participation by limiting their expression and participation in school activities based on their sex. Student participation must, therefore, be promoted to ensure parity that expression and action is exercised equally among girls and boys.